Analysis Of The Effectiveness Of Imposing Electronic Stamp Duty In An Effort To Optimize Taxpayer Compliance - Flora Sania; Heasty Olyvia Tambunan; Jihan Pahena Jariakh; Diah Kusumaningtyas; Yunia Ayu Ningtias (CV. AFDIFAL MAJU BERKAH, 2025)
Digital transformation in the national taxation system encourages the introduction of electronic stamp duty (e-stamp) as a modern fiscal instrument. This study aims to evaluate the effectiveness of e-stamp in improving taxpayer compliance and supporting the optimization of state revenue. The method used is a systematic literature review of a number of relevant legal sources, scientific journals, and current policies. The findings show that e-stamp has obtained legal legitimacy equivalent to physical stamps and functions as valid evidence in court, as regulated in PP No. 86 of 2021. In addition to accelerating transactions, e-stamp also strengthens transparency and accountability of tax administration. However, its utilization still faces obstacles in the form of limited technical regulations and low digital literacy of the community. For this reason, continuous education support and cross-sector synergy are needed to ensure effective and sustainable implementation.